Periodic Epileptiform Discharges in Children With Advanced Stages of Progressive Myoclonic Epilepsy. (October 2016) - Isobe, Natsumi; Sakai, Yasunari; Kira, Ryutaro; Sanefuji, Masafumi; Ishizaki, Yoshito; Sakata, Ayumi; Sasazuki, Momoko; Torio, Michiko; Akamine, Satoshi; Torisu, Hiroyuki; Hara, Toshiro
Huntington's disease (HD) and dentatorubral-pallidoluysian atrophy (DRPLA) are monogenic forms of neurodegenerative disorders with autosomal dominant inheritance. Compared with adult-onset HD and DRPLA, children with these disorders are more severely affected and are known to manifest the devastating symptoms of progressive myoclonic epilepsy (PME) syndrome. In this report, we present a 6-year-old girl with HD from a family, and 2 siblings with DRPLA from another unrelated family. Serial neuroimaging and electroencephalography (EEG) studies showed that periodic epileptiform discharges and synchronized paroxysmal activity became prominent with their disease progression. Periodic complexes in EEG may emerge at advanced stages of childhood PME as a consequence of rapidly degenerating processes of their brain functions.